2011
DOI: 10.1017/s0033822200034561
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Presence of Humic Substances in Wool and Silk by the Use of Nondestructive Fluorescence Spectroscopy: Quality Control for14C Dating of Wool and Silk

Abstract: ABSTRACT. Radiocarbon dating of degraded wool and silk provides 14 C results of questionable reliability. In most cases, degraded wool/silk contains humic substances (HSs). Thus, a nondestructive fluorescence spectroscopy method, using a fiberoptic probe, was developed to monitor the presence of HSs in degraded wool and silk. This method can provide information about the presence of HSs before and after pretreatment and about the 14 C age reliability. This study suggests considering with care wool/silk samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The samples prepared for pilot study 1 were analysed with spectrofluorescence before and after nanofiltration to determine the best filtration technique to remove HSs [19]. Based upon the results of these analyses it was decided to set up pilot study 2 wherein the samples were cross flow nanofiltrated on a downscaled installation and 14 C dated to verify the HS removal and the filter efficiency ( Fig.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The samples prepared for pilot study 1 were analysed with spectrofluorescence before and after nanofiltration to determine the best filtration technique to remove HSs [19]. Based upon the results of these analyses it was decided to set up pilot study 2 wherein the samples were cross flow nanofiltrated on a downscaled installation and 14 C dated to verify the HS removal and the filter efficiency ( Fig.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The brown color of the contaminated samples Beerlegem, Baldwin 46, and Baldwin 43 are likely due to the presence of humic substances, as shown by nondestructive spectrofluorescence analyses in Boudin et al (2011Boudin et al ( , 2014, and also demonstrated by the decrease of C:N ratio of the permeate after cross-flow nanofiltration as well as the good agreement of the 14 C date with the presumed historical date.…”
Section: C:n Analyses Of Modern Wool and Silkmentioning
confidence: 79%
“…The standard pre-treatments are ABA for charcoal, solvent extraction for wool, silk and leather [1], ABA and/or NaClO2 bleaching for wood, collagen extraction following Longin [2] plus NaOH-wash for bone samples, and HCl and acetic acid treatment for bone apatite and cremated bones [3].…”
Section: Sample Pre-treatment and Graphitisationmentioning
confidence: 99%